Measuring what matters: Actionable information for conservation biocontrol in multifunctional landscapes - Chaplin-Kramer, Rebecca; O’Rourke, M.; Zhang, Wei; Robinson, B.; Schellhorn, Nancy A. (Frontiers Media, 2019)
Despite decades of study, conservation biocontrol via manipulation of landscape elements has not become a mainstream strategy for pest control. Meanwhile, conservation groups and governments rarely consider the impacts of land management on pest control, and growers can even fear that conservation biocontrol strategies may exacerbate pest problems. By finding leverage points among these actors, there may be opportunities to align them to promote more widespread adoption of conservation biological control at the landscape-scale. But are ecologists measuring the right things and presenting the right evidence to enable such alignment? We articulate key concerns of growers, conservation groups, and governments with regards to implementing conservation biological control at the landscape scale and argue that if ecologists want to gain more traction, we need to reconsider what we measure, for what goals, and for which audiences. A wider set of landscape objectives that ecologists should consider in our measurements include risk management for growers and co-benefits of multifunctional landscapes for public actors. Ecologists need to shift our paradigm toward longer-term, dynamic measurements, and build cross-disciplinary understanding with socioeconomic and behavioral sciences, to enable better integration of the objectives of these diverse actors that will be necessary for landscape management for conservation biocontrol to achieve its full potential.